Investigation Of Short-Circuit Electromagnetic Force In Three-Phase Busbar System - Yusop, Farhana Mohamad (2013)
Busbar system is an effective tool for distributing electricity up to a few kA from the main switch room to the load. Therefore, it should be integrated with a well-known characteristic that can give confidence to the consumer to use the distribution system. A short-circuit test is one of the very important parameters to ensure the system is able to withstand electromagnetic force due to short-circuit current for a definite time. Thus far, Malaysian manufacturers are compelled to send their products outside to do short-circuit tests due to Malaysia’s inability to provide the facilities. The cost alone for performing short-circuit tests is considered high and take much time, and will continue to increase if the products having failure. To overcome this issue, studies on the prediction of electromagnetic force due to short-circuit current is highly necessary. Electromagnetic forces on rigid bare conductor busbars due to short-circuit currents are calculated based on IEC Standard 60865/93. Meanwhile, finite element analysis is performed in order to estimate the electromagnetic force on the busbar system. This analysis is considered under steady-state and transient short-circuit current which also involves a 3P5W of single, double and triple stack busbar system. The magnetic flux distributions are analyzed and the performance of the busbar system is identified based on the electromagnetic force generated under peak short-circuit currents. The simulation results of the electromagnetic force have shown good performance with numerical calculations. It is revealed that modification in the configuration of busbar conductor and dimensional arrangement of busbar system by an increment of 1mm result in a reduction of electromagnetic force on the conductors up to 3% -7%.